Good Bids Come to Those Who Wait: The Value of Late Bidding in Online Auctions. Issue 309 (7th March 2019) - Lim, Bryan; Shemesh, Joshua
Abstract : This paper proposes an intuitive rationale for late bidding in online venues. The expected surplus from bidding on subsequent auctions for equivalent items creates an option value to losing the current auction. This option is dynamic due to the stochastic arrival of new auctions and early bids on later‐closing auctions. We demonstrate that late bidding can be optimal given the decentralised and heterogeneous nature of online auctions, in which the option value is exogenous to an individual bidder's actions. Late bidding precludes the bidder from being locked into a suboptimal bid as her opportunity set evolves.